Spinal metastases from thyroid cancer: Some prognostic factors. Issue 1 (January 2022) - Planty-Bonjour, Alexia; Dubory, Arnaud; Terrier, Louis-Marie; Taïbi, Thiziri; Cook, Ann-Rose; Cristini, Joseph; Buffenoir, Kévin; Pascal-Moussellard, Hugues; Carpentier, Alexandre; Le Nail, Louis-Romée; Mathon, Bertrand; Amelot, Aymeric
Abstract: Background: Spinal metastases (SpMs) from thyroid cancers (TC) significantly reduce quality of life by causing pain, neurological deficits in addition to increasing mortality. Moreover, prognosis factors including surgery remain debated. Methods: Data were stored in a prospective French national multicenter database of patients treated for SpM between January 2014 and 2017. Fifty-one consecutive patients affected by TC with 173 secondary SpM were included. Results: Mean overall survival (OS) time for all patients from the diagnosis of a thyroid SpM event was 9.1 years (SD 8.7 months). The 1-year, 5-year and 10-year survival estimates were 94% (SD 3.3), 83.8.0% (SD 5.2), and 74.5% (SD 9.9). The median period of time between primary thyroid tumor diagnosis and the SpM event was 31.4 months (SD 71.6). In univariate analysis, good ECOG-PS (status 0 and 1) (p < 0.0001), ambulatory status (Frankel score) (p < 0.0001) and no epidural involvement (p = 0.01), were associated with longer survival, whereas cancer subtype (p = 0.436) and spine surgery showed no association (p = 0.937). Cox multivariate proportional hazard model only identified good ECOG-PS: 0 [HR: 0.3, 95% CI 0.1–0.941; p < 0.0001], 1 [HR: 0.8, 95% CI 0.04–2.124; p = 0.001] and ambulatory neurological status: Frankel E [HR: 0.262, 95% CI 0.048–1.443; p = 0.02] to be independent predictors of better survival. Conclusion: For cases presenting SpM from TC, we highlighted that the only prognostic factors were the progression of the cancer (ECOG-PS) and the clinical neurological impact of the SpM (Frankel status). Surgery should be discussed mainly for stabilization and neurological decompression.